The effect of inspiratory muscle training on the quality of life, immune response, inspiratory and lower limb muscle strength of older adults: a randomized controlled trial - Vilaça,Adriano Florencio (2019)
Abstract Objective: To evaluate the impact of inspiratory muscle training (IMT) on the quality of life, immune response, inspiratory and lower limb muscle strength of older adults. Method: A randomized clinical trial was conducted with 30 institutionalized older adults. They were allocated into two groups: the IMT group (n=15), which underwent IMT with PowerBreathe Classic, using a load of 60% of maximal inspiratory pressure (MIP). This was performed using a 30 repetition protocol, three times a week, for six weeks. The second group was the control group (n=15) which did not perform any type of therapeutic intervention. In both groups, MIP, lower limb strength by sit-up test, quality of life by the SF-36 questionnaire and C-reactive protein (CRP) were evaluated. Results: The results demonstrated the homogeneity between the groups regarding the demographic and clinical variables. The IMT group showed an increase in the variation of MIP (9.20±7.36 cmH2O) compared to the control (0.93±8.79 cmH2O). Improvement was also observed in the sitting and standing test (p<0.05) (Tukey Test) in the difference between the values ​​before and after the IMT. In terms of quality of life, two of the eight SF-36 domains were influenced by the IMT, namely: functional capacity and limitations due to physical factors. There were no changes in CRP in either group. Conclusion: IMT improved the inspiratory muscle strength, lower limb strength and quality of life of institutionalized older adults. These findings reinforce the contribution of this therapy to reducing the deleterious effects of aging.